The Integration of Traditional Values of Pelintau Pencak Silat as a Resource for Local History Education - Prasetyo, Okhaifi; Dilwan, Muhammad Al; Rahman, Aulia (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2024)
The traditional values of Pencak Silat Pelintau have not been systematically incorporated into the curriculum as a resource for local history education. The integration of these values is essential for enhancing the relevance of local learning materials and ensuring the availability of indigenous educational resources. This study seeks to explore the integration of Pencak Silat Pelintau’s traditional values into the curriculum as an approach to local history education. Employing a descriptive qualitative research design, the study utilized data collection methods including observation, interviews, and document analysis. Data were analyzed through processes of data reduction, data presentation, and conclusion drawing. The findings suggest that the local wisdom inherent in Pencak Silat Pelintau can be effectively integrated into local history instruction. Within the framework of the Merdeka Curriculum, the topics of the Islamic Kingdoms in Phase E and Colonialism and Indonesian National Resistance in Phase F present appropriate opportunities to incorporate the stories and values of the Pelintau Pencak Silat tradition. This integration enables students to develop a deeper understanding of local history while internalizing key values such as honesty, discipline, cooperation, simplicity, politeness, courage, and resilience—values that contribute to shaping positive attitudes and behaviors in students' personal and social lives. Abstrak: Nilai-nilai tradisional Pencak Silat Pelintau belum diintegrasikan secara sistematis ke dalam kurikulum sebagai sumber pembelajaran sejarah lokal. Integrasi nilai-nilai ini sangat penting untuk meningkatkan relevansi materi pembelajaran lokal dan memastikan tersedianya sumber daya pendidikan yang bersifat lokal. Penelitian ini bertujuan untuk mengkaji integrasi nilai-nilai tradisional Pencak Silat Pelintau ke dalam kurikulum sebagai pendekatan dalam pembelajaran sejarah lokal. Dengan menggunakan desain penelitian kualitatif deskriptif, penelitian ini mengumpulkan data melalui metode observasi, wawancara, dan analisis dokumen. Data dianalisis melalui proses reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kearifan lokal yang terkandung dalam Pencak Silat Pelintau dapat diintegrasikan secara efektif ke dalam pengajaran sejarah lokal. Dalam kerangka Kurikulum Merdeka, topik-topik mengenai Kerajaan Islam pada Fase E serta Kolonialisme dan Perlawanan Nasional Indonesia pada Fase F menjadi peluang yang tepat untuk mengintegrasikan cerita dan nilai-nilai tradisi Pencak Silat Pelintau. Integrasi ini memungkinkan siswa untuk memperoleh pemahaman yang lebih dalam mengenai sejarah lokal sekaligus menginternalisasi nilai-nilai penting seperti kejujuran, disiplin, kerjasama, kesederhanaan, kesopanan, keberanian, dan ketangguhan—nilai-nilai yang berkontribusi dalam membentuk sikap dan perilaku positif dalam kehidupan pribadi dan sosial siswa.